2014
DOI: 10.4141/cjps2013-403
|View full text |Cite
|
Sign up to set email alerts
|

Canada fleabane (Conyza canadensis) control with preplant applied residual herbicides followed by 2,4-D choline/glyphosate DMA applied postemergence in corn

Abstract: Ford, L., Soltani, N., Robinson, D. E., Nurse, R. E., McFadden, A. and Sikkema, P. H. 2014. Canada fleabane (Conyza canadensis) control with preplant applied residual herbicides followed by 2,4-D choline/glyphosate DMA applied postemergence in corn. Can. J. Plant Sci. 94: 1231–1237. Glyphosate resistant (GR) Canada fleabane (Conyza canadensis) is an extremely problematic weed in no-tillage farming operations. A total of five field trials were conducted over a 2-yr (2012 and 2013) period in Ontario to determine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
24
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

7
2

Authors

Journals

citations
Cited by 18 publications
(29 citation statements)
references
References 22 publications
3
24
2
Order By: Relevance
“…Davis et al (2010) reported that spring applications of saflufenacil provided excellent control of Canada fleabane by reducing densities more than 90%. The results from this study are also similar to the results reported by Ford et al (2014), who found that saflufenacil/ dimethenamid-p applied PP provided control of GR Canada fleabane that was similar to weed-free treatment.…”
supporting
confidence: 90%
See 1 more Smart Citation
“…Davis et al (2010) reported that spring applications of saflufenacil provided excellent control of Canada fleabane by reducing densities more than 90%. The results from this study are also similar to the results reported by Ford et al (2014), who found that saflufenacil/ dimethenamid-p applied PP provided control of GR Canada fleabane that was similar to weed-free treatment.…”
supporting
confidence: 90%
“…treatment with atrazine, flumetsulam, and s-metolachlor/atrazine. Ford et al (2014) reported that s-metolachlor/atrazine (1800 g a.i. ha −1 ) did not provide effective control of GR Canada fleabane, which is consistent with the results from this study.…”
mentioning
confidence: 99%
“…Any visible crop injury symptoms in these studies did not affect corn yield. Left uncontrolled, GR Canada fleabane reduced corn grain yields by up to 50% in this study, which is similar to research by Ford et al [48] that observed a 69% yield loss due GR Canada fleabane interference in corn.…”
Section: Discussionsupporting
confidence: 91%
“…ha provided 97% to 99% control of GR Canada fleabane. In contrast, Ford et al (2014) reported that glyphosate plus isoxaflutole plus atrazine (900 + 52.5 + 500 g a.i. ha 1 ) provided variable control of GR Canada fleabane ranging from 27 to 97% in corn.…”
Section: Biologically Effective Dose Of Isoxaflutole and Metribuzin Cmentioning
confidence: 91%